A formação regional do bico do papagaio: regionalização e polarização - Almeida, Rutileia Lima (2010)
The Bico do Papagaio is an area of the State of Tocantins that is configured as a confluence zone with the states of Maranhão and Pará, forming an access channel, through Belém-Brasília, for people, goods and information of the Center-south to the North of the country. According to the Department of Development of the State of Tocantins (SEPLAN-TO), Bico do Papagaio is a political-administrative area composed by 25 municipal districts. The Ministry of the National Integration already understands that the area surpasses the borders of the State of Tocantins, by its North end and also that it goes to the Southwest of Maranhão and the Southeast of Pará. This last division is also assumed by the common sense, for the civil society and for politicians, what is justified historically for the bows built, because of its occupation process and geographical approaches, whose space, material and symbolically contiguous, is characterized by an important functional coherence. In this sense, our objective is to accomplish a study of the regional formation of Bico do Papagaio, considering the socioeconomic relationships that extrapolate the political-administrative limits of the official regionalization. This analysis perspective implicates in considering the functions of the urban and regional net and the population mobility. For so much, it inserts the study of the polarization in this analysis. Although the focus of this study is the regional formation, the established temporary cutting for this approach starts in 1988, year of the territorial division of the State of Goiás.